Increased AHR Transcripts Correlate With Pro-inflammatory T-Helper Lymphocytes Polarization in Both Metabolically Healthy Obesity and Type 2 Diabetic Patients - Zhao, Ru-xing; He, Qin; Sha, Sha; Song, Jia; Qin, Jun; Liu, Peng; Sun, Yu-jing; Sun, Lei; Hou, Xin-guo; Chen, Li (Frontiers in Immunology, 2020)
Aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor whose activity is regulated by small molecules provided by diet, xenobiotics and metabolism. It has been proven to be involved in energy homeostasis and inflammation in most recent years. Epidemiologically, exposure to xenobiotic AHR ligands is linked to obesity and type 2 diabetes (T2D). AHR is also the key transcription factor determining the lineage commitment of pro-inflammatory Th17 and Th22 cells from naïve CD4+ T cells. It has been well-illustrated in animal models that IL-22, the major effector cytokine of Th17 and Th22 cells, played a major role in the interaction of gut microbiota and metabolism. But there were still missing links between gut microbiota, IL-22, and metabolism in humans. Our previous findings indicated that elevated circulating levels of IL-22 and frequencies of Th22 cells were associated with insulin resistance in both patients with obesity and T2D. Additionally, the hyperactive Th17 and Th22 cells phenotype also correlate with islets β-cell dysfunction in T2D. In this study, we made efforts to determine AHR expressions in peripheral blood mononuclear cells (PBMCs) from patients with T2D and metabolically healthy obesity (MHO). Correlation analyses were conducted to assess the possible link between AHR and the metabolic and inflammatory context. We revealed that mRNA expression of AHR was up-regulated and correlated with the percentage of Th17, Th22 as well as Th1 cells. Elevated plasma levels of IL-22 and IL-17 also correlated with increased AHR transcripts in PBMCs from both MHO and T2D patients. The transcription factor AHR may thus have a plausible role in the interaction between metabolism and pro-inflammatory status of patients in the development of obesity and T2D.